1995
DOI: 10.1007/bf02251224
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of the effects of inhibition of MAO-A versus MAO-B on striatal L-DOPA and dopamine metabolism

Abstract: Utilizing the cerebral microdialysis technique, we have compared in vivo the effects of selective MAO-A, MAO-B, and nonselective MAO inhibitors on striatal extracellular levels of dopamine (DA) and DA metabolites (DOPAC and HVA). The measurements were made in rats both under basal conditions and following L-DOPA administration. Extracellular levels of dopamine were enhanced and DA metabolite levels strongly inhibited both under basal conditions and following L-DOPA administration by pretreatment with the nonse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…However, if CORT is inhibiting DA metabolism, this inhibition is not sufficient to provide enough regulatory feedback to produce corresponding changes in DA synthesis or turnover. In support of this possibility, basal extracellular DA concentrations remain stable with selective inhibition of MAO-B (Brannan et al 1995). CORT also inhibits peripheral catecholamine metabolite concentrations, similar to the decrease in central DA utilization observed here.…”
Section: Discussionsupporting
confidence: 81%
“…However, if CORT is inhibiting DA metabolism, this inhibition is not sufficient to provide enough regulatory feedback to produce corresponding changes in DA synthesis or turnover. In support of this possibility, basal extracellular DA concentrations remain stable with selective inhibition of MAO-B (Brannan et al 1995). CORT also inhibits peripheral catecholamine metabolite concentrations, similar to the decrease in central DA utilization observed here.…”
Section: Discussionsupporting
confidence: 81%
“…Brannan et al (13) and Kaseda et al (14) demonstrated that selegiline treatment in rats and primates markedly increases DA level in dialysates after L-DOPA treatment. These studies confirm the usefulness of selegiline as an adjunct to L-DOPA, but also suggest the difficulty in deciding the clinical dose of L-DOPA for selegiline-treated patients for maintaining brain DA level in a safe level between the therapeutic threshold and the adverse reaction threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The data with clorgyline recall that MAO A is mainly involved in the regulation of the dopaminergic system in the striatum [13][14][15][16][17][18] , but, elsewhere, its role in the metabolism of DA and of 5-HT is region-dependent 8,16 . The lack of effect of clorgyline on NE tissue content is not surprising because it usually requires higher non-selective doses or chronic treatment to have a pronounced effect.…”
Section: Resultsmentioning
confidence: 94%